Adab dalam Menuntut Ilmu Menurut Perspektif Syeikh Muhammad Syakir dalam Kitab Washoya Al Abaa’ Lil Abnaa - Eva Defani Suti; Eko Surbianto; Khambali (UNISBA Press, 2022)
Abstract. The Indonesian nation is currently reaching its peak in facing various educational problems, especially the decline of morals and the loss of adab. Adab can be interpreted as a reflection of a person's good or bad. The word adab is usually addressed specifically to pupils. Students are defined as people who want to gain knowledge. Science is a knowledge that can provide instructions for a person to understand between right and wrong, as well as the provision of man to obtain salvation and well-being both in the world and in the hereafter. Based on this phenomenon, the problem in this study is formulated as follows: